2013
DOI: 10.1007/s12017-013-8254-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Histone Lysine Methyltransferases SUV39H1 and SETDB1 in Gliomagenesis: Modulation of Cell Proliferation, Migration, and Colony Formation

Abstract: Posttranslational modifications of histones are considered as critical regulators of gene expression, playing significant role in the pathogenesis and progression of tumors. Trimethylation of histone 3 lysine 9 (H3K9me3), a repressed transcription mark, is mainly regulated by the histone lysine N-methyltransferases (HKMTs), SUV39H1 and SETDB1. The present study investigated the implication of these HKMTs in glioma progression. SUV39H1 and SETDB1 expression was upregulated in glioma cell lines (GOS-3, 1321N1, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
63
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 54 publications
10
63
1
1
Order By: Relevance
“…SETDB1 has been established as an oncogene in a number of human carcinomas. A study has demonstrated the role of histone lysine methyltransferases SUV39H1 and SETDB1 in gliomagenesis and its association with cell proliferation, migration, and colony formation (43). Another study found that SETDB1 positively stimulated the WNT/β-catenin pathway and decreased P53 expression, resulting in enhanced non-small cell lung cancer growth in vitro and in vivo (44).…”
Section: Discussionmentioning
confidence: 99%
“…SETDB1 has been established as an oncogene in a number of human carcinomas. A study has demonstrated the role of histone lysine methyltransferases SUV39H1 and SETDB1 in gliomagenesis and its association with cell proliferation, migration, and colony formation (43). Another study found that SETDB1 positively stimulated the WNT/β-catenin pathway and decreased P53 expression, resulting in enhanced non-small cell lung cancer growth in vitro and in vivo (44).…”
Section: Discussionmentioning
confidence: 99%
“…15 glioma cell lines and in glioma tissues compared with normal brains which correlated with histological malignancy. Treatments that altered SUV39H1 and SETDB1 expression affected proliferative and apoptotic potential as well as migratory and colony formation capacity of glioma cells [39].…”
Section: Misregulation Of Histone-modifying Enzymes In Gliomasmentioning
confidence: 96%
“…H3S10ph AURKB Increased activity [27] H3K27me2,3 EZH2 Overexpression [33][34][35][36][37][38] H3Y41ph JAK2 Increased activity [27] H3K9me3 KMT1E (SETDB1) Overexpression [39] H3K36me3 KMT3A (SETD2) Mutation [40] H3K4me1 KMT7 (SETD7) Mutation [28] H3T6ph PKCβ Increased activity [27] H3T11ph PKM2 Overexpression [41] H4R3me2 PRMT1 Overexpression [42] H3K9me3 SUV39H Overexpression [39] Erasers Pan-histone acetylation HDAC2 Mutation [28] Pan-histone acetylation HDAC4 Downregulation [32] Pan-histone acetylation HDAC5 Downregulation [32] Pan-histone acetylation HDAC6 Downregulation [32] Pan-histone acetylation HDAC7 Downregulation [32] Pan-histone acetylation HDAC9 Downregulation Mutation [32] [ 28] pan-histone acetylation HDAC11 Downregulation [32] H3K4me1,2; H3K9me1,2 KDM1 (LSD1) Overexpression [43] H3K9me1,2 KDM3A (JMJD1A) Mutation [28] H3K9me1,2 KDM3B (JMJD1B) Mutation [28] H3K4me1,2,3 KDM5B (JARID1B) Overexpression [44] H3K27me3 KDM6B (JMJD3) Overexpression [45] Readers…”
Section: Writersmentioning
confidence: 99%
“…SETDB1 immunohistochemistry correlated with clinical characteristics in one study (Kostaki et al, 2014), while a study with a similar approach identified prognostic significance for G9A (EHMT2), but not SETDB1 expression (Miura et al, 2014). A functional role for SETBP1 and SUV39 has also been proposed in glioma and prostate cancer (Spyropoulou et al, 2014;Sun et al, 2014). Modulation of H3K9 methylation is also a critical downstream mechanisms of mutant IDH in glioma (as discussed below), and the effect of MLLfusions and DOT1L in MLL-rearranged leukemias (as discussed above).…”
Section: Modulation Of Global and Locus-specific H3k9 Methylation By mentioning
confidence: 97%